Lepiota baiyunensis sp. nov. (Agaricales, Agaricaceae) from Baiyun Mountain, China - Liang, Ying-Shan; Xu, Yi-Wen; Ouyang, Min; Huang, Xiao-Xia; Lin, Zhi-Jun; Qiu, Li-Hong (Phytotaxa, 2023)
A novel species of Lepiota sect. Ovisporae from Baiyun Mountain, Guangzhou, China is described, based on phylogenetic analysis of both internal transcribed spacer region (ITS) and multi-loci (ITS, LSU, IGS and mtSSU) combined with morphological examinations. Lepiota baiyunensis sp. nov. differs from Lepiota lilacea by its light yellow lamellae, stipe covered with lamellar squamules, lacking true annulus, usually clavate cheilocystidia and trichodermal pileus covering composed of long, cylindrical elements.